HIGH MOBILITY GROUP BOX-1 LEVELS IN SCHIZOPHRENIA: POTENTIAL BIOMARKER OF REMISSION PHASE : High mobility group box-1 levels in Schizophrenia - Yilmaz, Nuryil; Yelboga, Zekeriya; Yilmaz, Yavuz; Demirpence, Ozlem (Journal of Medical Biochemistry, 2020)
Background: Schizophrenia is a chronic mental disorder, characterized by acute exacerbation and remission phases. Immune system has a role in the pathophysiology of schizophrenia. High mobility group box-1 (HMGB-1)  is a macrophage secreted protein activating immune cells to produce cytokines. The aim of this study was to evaluate HMGB-1 levels among patients with schizophrenia both in acute exacerbation and remission phases.Methods: Consecutive schizophrenia patients in acute exacerbation and remission phases were enrolled and compared with each other and with age-sex matched healthy subjects. Patients were assessed with the Scale for the Assessment of Positive Symptoms (SAPS), Scale for the Assessment of Negative Symptoms (SANS), Brief Psychiatric Rating Scale (BPRS), Clinical Global Impression Scale (CGI).Results: Mean HMGB-1 levels were not significantly different in acute exacerbation phase versus remission phase schizophrenia patients (2139±564 pg/ml vs. 2326±471 pg/ml, p=0.335) and both were individually higher than the control group (1791±444 pg/ml, p=0.05 for acute exacerbation vs control, p=0.002 for remission vs control). In remission phase schizophrenic patients, HMGB-1 levels were positively correlated with Scale For The Assessment of Positive Symptoms (r=0.447, p=0.015) and BPRS (r=0.397, p=0.033) scores and HMGB-1 levels were independently associated with BPRS.Conclusion: Serum HMGB-1 levels were shown to be increased in patients with schizophrenia patients irrespective of phase and HMGB-1 levels were related to symptom severity according to psychiatric scales among patients in remission phase of schizophrenia.
Keywords: schizophrenia, HMGB-1, Remission and acute exacerbation phase.